2021
DOI: 10.1016/j.ica.2021.120287
|View full text |Cite
|
Sign up to set email alerts
|

Are vanadium complexes druggable against the main protease Mpro of SARS-CoV-2? – A computational approach

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 72 publications
1
11
0
1
Order By: Relevance
“…Additionally, it is important to mention that recent work from Aureliano's group about melanoma anticancer activity of a variety of vanadium compounds [73] and potential anti-SARS-CoV-2 activity of vanadium compounds by Scior et al [74], present a promising future for vanadium compounds as metallodrugs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is important to mention that recent work from Aureliano's group about melanoma anticancer activity of a variety of vanadium compounds [73] and potential anti-SARS-CoV-2 activity of vanadium compounds by Scior et al [74], present a promising future for vanadium compounds as metallodrugs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, silver graphene (GO-Ag) oxide has shown antiviral effects against enveloped and non-enveloped viruses even more than Ag alone [1,99]. Vanadium can stimulate the activation of T cells [116], and bismuth has an inhibitory effect on helix unwinding and ATPase activity of SARS-CoV-2 nsp13 [27], so these metals might be useful in the treatment of COVID-19. About gallium there are two ideas, some studies believe that gallium has an anti-inflammatory and antiviral activity against SARS-CoV-2 and inhibits viral replication [119][120][121][122][123], but other studies believe that there is no relation between gallium uptake and COVID-19 related disorders [118].…”
Section: Discussionmentioning
confidence: 99%
“…Vanadium polyoxide clusters have a good antiviral effect. Also, due to their nuclear properties, they can be a suitable contrast agent that can be used in imaging and better detection of radiological images [116]. Vanadium-based drugs are considered today because they are both less toxic and can have biological activities such as anti-diabetic and anti-cancer properties [117].…”
Section: Vanadiummentioning
confidence: 99%
“…As is known to all, some trace metal elements benefit from regulating the body’s immune response and enhancing resistance [ 27 , 29 33 , 35 , 36 ]. Therefore, metal nutrients will play an essential and beneficial role in alleviating excessive inflammation and producing neutralizing antibodies.…”
Section: Overview Of Covid-19 and Sars-cov-2mentioning
confidence: 99%
“…6 ). Scior et al [ 35 ] conducted computer simulations and reported that some vanadium complexes could combine with the major protease (M pro ) of SARS-CoV-2 to inhibit virus replication. Gold metallodrugs are efficient inhibitors of SARS-CoV-2’s papain-like protease (PL pro ), which plays a key role in virus replication [ 36 ].…”
Section: Metal-related Prevention and Treatment Strategiesmentioning
confidence: 99%